2017
DOI: 10.12659/msm.902704
|View full text |Cite
|
Sign up to set email alerts
|

Jolkinolide A and Jolkinolide B Inhibit Proliferation of A549 Cells and Activity of Human Umbilical Vein Endothelial Cells

Abstract: BackgroundJolkinolide A (JA) and Jolkinolide B (JB) are diterpenoids extracted from the roots of Euphorbia fischeriana Steud and have been shown to have anti-tumor activity. However, their effects on the ability of tumor cells to invade blood vessels and metastasize remain largely unknown. Investigations into the effects of JA and JB on the angiogenesis of tumor tissues may facilitate the identification of new natural drugs with anti-tumor growth and metastasis activities.Material/MethodsWe used different conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Jokinolide B has been shown to have de nite anti-tumor activity [19][20][21][22]. It has extracted several monomeric components from E. scheriana, such as Jolkinolide A [23], 17-acetoxyjolkinolide B [24], 17-hydroxyjolkinolide B [25], 12-Deoxyphorbol-13-palmitate [18, 26-27], and Jokinolide B, and proved to have signi cant anti-tumor activity from different directions. Therefore, in our study, herbal medicinal compound prescribe were selected as research object re ects the scienti c connotation of Chinese herbal with multiple components, multiple effects and multiple targets.…”
Section: The Quality Control Of Eszm Extractmentioning
confidence: 99%
“…Jokinolide B has been shown to have de nite anti-tumor activity [19][20][21][22]. It has extracted several monomeric components from E. scheriana, such as Jolkinolide A [23], 17-acetoxyjolkinolide B [24], 17-hydroxyjolkinolide B [25], 12-Deoxyphorbol-13-palmitate [18, 26-27], and Jokinolide B, and proved to have signi cant anti-tumor activity from different directions. Therefore, in our study, herbal medicinal compound prescribe were selected as research object re ects the scienti c connotation of Chinese herbal with multiple components, multiple effects and multiple targets.…”
Section: The Quality Control Of Eszm Extractmentioning
confidence: 99%
“…It has been proved that the Akt/mTOR signaling pathway is a crucial regulator of glycometabolic homeostasis . Published articles reported that JB reduced the expression of vascular endothelial growth factor (VEGF) which is important for tumor growth . The expression levels of Akt, STAT3, and mTOR proteins were also inhibited by JB in A549 cells, indicating that JB suppressed VEGF expression via inhibiting the Akt‐STAT3‐mTOR pathway .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, JB was demonstrated to possess anti‐metastatic effect on breast cancer cells via inhibiting MAPK/ERK pathway . JB also inhibited the growth and metastasis of lung cancer through inhibiting the Akt/STAT3/mTOR signaling pathway . Moreover, JB was reported to induce apoptosis and inhibit tumor growth in mouse melanoma B16F10 cells by altering glycolysis .…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory effect of jolkinolide B is more obvious than that of jolkinolide A. The medium of A549 cells stimulated with either jolkinolide A or jolkinolide B was found to inhibit the proliferation and migration of human umbilical vein endothelial cells (HUVECs) in a concentration dependent manner [ 10 ]. Parthenolide ( 3 ), a sesquiterpene lactone extracted from Tanacetum parthenium , was shown to inhibit the proliferation of A549 cells in the absence and presence of nicotine.…”
Section: Effects Of Natural Products On the Tumor Microenvironmentmentioning
confidence: 99%